2021
DOI: 10.1186/s12935-021-01893-0
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages-derived exosomal lncRNA LIFR-AS1 promotes osteosarcoma cell progression via miR-29a/NFIA axis

Abstract: Background Osteosarcoma (OS) is the most common primary malignant bone tumor in young people. Tumor-associated macrophages (TAMs) have been reported to play an important role in the development of osteosarcoma. However, the detailed molecular mechanisms remain largely unknown and need to be elucidated. Recently, exosomes have been reported as the crucial mediator between tumor cells and the tumor microenvironment. And a lot of lncRNAs have been reported to act as either oncogenes or tumor suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 33 publications
0
37
0
Order By: Relevance
“…In pancreatic cancer, studies have shown that the blocking Sbf2-AS1 in M2 macrophage-derived exosomes inhibited XIAP expression through the negative regulation of miR-122-5p, and played a role in reducing the oncogenic ability of tumor cells ( 81 ). In the report by Zhang et al., RNA sequencing and other methods were used to identify differentially expressed miRNAs and lncRNAs in MΦ-CM co-cultured osteosarcoma cells and the corresponding control group, which confirmed that lncRNA LIFR-AS1 was upregulated in MΦ-CM co-cultured osteosarcoma cells ( 97 ). In addition, LIFR-AS1 can be transmitted from macrophages to osteosarcoma cells via exosomes, and promote tumor progression via spongy transfection of miR-29a ( 97 ).…”
Section: Lncrna Regulation Of the Time: Focus On Immune Escapementioning
confidence: 79%
See 2 more Smart Citations
“…In pancreatic cancer, studies have shown that the blocking Sbf2-AS1 in M2 macrophage-derived exosomes inhibited XIAP expression through the negative regulation of miR-122-5p, and played a role in reducing the oncogenic ability of tumor cells ( 81 ). In the report by Zhang et al., RNA sequencing and other methods were used to identify differentially expressed miRNAs and lncRNAs in MΦ-CM co-cultured osteosarcoma cells and the corresponding control group, which confirmed that lncRNA LIFR-AS1 was upregulated in MΦ-CM co-cultured osteosarcoma cells ( 97 ). In addition, LIFR-AS1 can be transmitted from macrophages to osteosarcoma cells via exosomes, and promote tumor progression via spongy transfection of miR-29a ( 97 ).…”
Section: Lncrna Regulation Of the Time: Focus On Immune Escapementioning
confidence: 79%
“…In the report by Zhang et al., RNA sequencing and other methods were used to identify differentially expressed miRNAs and lncRNAs in MΦ-CM co-cultured osteosarcoma cells and the corresponding control group, which confirmed that lncRNA LIFR-AS1 was upregulated in MΦ-CM co-cultured osteosarcoma cells ( 97 ). In addition, LIFR-AS1 can be transmitted from macrophages to osteosarcoma cells via exosomes, and promote tumor progression via spongy transfection of miR-29a ( 97 ). These findings show that abnormally expressed lncRNAs can be used as potential biological targets for cancer therapy.…”
Section: Lncrna Regulation Of the Time: Focus On Immune Escapementioning
confidence: 79%
See 1 more Smart Citation
“…As a result, the growth, invasion and metastasis of osteosarcoma cells with low AXL expression were able to be promoted by osteosarcoma cells with high AXL expression ( Figure 2 ; Li Q. et al, 2020 ). Zhang et al reported that macrophages derived exosomal lncRNA LIFR-AS1 via the miR-29a/NFIA axis promoted osteosarcoma cell proliferation and invasion ( Zhang H. et al, 2021 ). Pan et al demonstrated that CDDP drug-resistant osteosarcoma cell derived exosomes could transfer hsa_circ_103801 to chemotherapy-sensitive osteosarcoma cells to enhance the resistance of osteosarcoma cells to CDDP ( Pan et al, 2021 ).…”
Section: The Functions Of Cargoes Derived From Exosomes In Osteosarcomamentioning
confidence: 99%
“…Han et al demonstrated that overexpression of AGAP1 could inhibit the function of exosomal miR-1307 in osteosarcoma ( Han et al, 2021 ). Zhang et al reported that exosomal lncRNA LIFR-AS1 promote osteosarcoma progression via the miR-29a/NFIA axis ( Zhang H. et al, 2021 ). The above studies highlight novel therapeutic targets for osteosarcoma.…”
Section: Potential Application Of Exosomes In Osteosarcomamentioning
confidence: 99%